Pengembangan Soal Setara AKM Domain Konten Data dan Ketidakpastian dengan Konteks Esport - Al Hasany, Muhammad Ilham Fauzi; Palupi, Evangelista Lus Windiyana (MATHEdunesa, 2025)
Mathematical literacy is an ability to formulate, use and interpret mathematics to solve problems in various real world contexts. Mathematical literacy not only helps in solving mathematical problems, but can be useful in everyday life such as helping students become more financially literate, increasing opportunities in the world of work and building a secure mathematical foundation, which can be built through lifelong learning. However, unfortunately students' mathematical literacy achievements in Indonesia are quite low. This is because students are not accustomed to working on AKM equivalent questions and also the AKM tryout provided by the government are so limited and can only be accessed by a few groups. Therefore, this research aims to describe the process of developing AKM equivalent questions so that teachers can create their own AKM questions which are useful for getting students used to working on them and produce AKM equivalent question packages that have good item validity and question reliability. The research method used is ADDIE model development research which has 5 stages, namely Analyze, Design, Develop, Implement and Evaluate. The focus of the question content in this research is the data content and uncertainty of phase D. The question context uses an Esport s context which focuses on the topic of the game Mobile Legends: Bang Bang. The final trial subjects of this research were 23 class VIII students at SMPN 24 Surabaya. The results of this research are part of the AKM equivalent question package which contains 11 questions, an answer key and scoring guidelines.